2021
DOI: 10.1021/acsomega.1c05921
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antibacterial Activity and Cell Viability of Ag/Mg and Ag/Zn Co-doped Hydroxyapatite Derived from Natural Limestone

Abstract: Improving the antibacterial activity to avoid infections and keeping the biocompatibility at a safe level of HAp-based materials is highly important for biomedical applications. In this work, we investigate the antibacterial activity of 2.5Ag/2.5Mg co-doped HAp and 2.5Ag/2.5Zn co-doped HAp toward Escherichia coli bacteria. Moreover, their biocompatibility for osteoblastic cells (MC3T3-E1 cells) was also evaluated. The physical properties were characterized with necessary characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Several previous studies have reported the antimicrobial properties of Zn-nHAp against Staphylococcus aureus and Escherichia coli [ 25 , 57 , 62 , 72 , 73 , 74 ]. Multiple factors could contribute to this bactericidal effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported the antimicrobial properties of Zn-nHAp against Staphylococcus aureus and Escherichia coli [ 25 , 57 , 62 , 72 , 73 , 74 ]. Multiple factors could contribute to this bactericidal effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some studies used PLGA to encapsulate antibacterial agents which significantly reduced bacterial growth [ 53 , 54 , 55 ], but this could increase the burden of antibiotic-resistant bacterial species, and also raise the concern of a burst release of the encapsulated antibiotic [ 56 ]. Silver and copper ions (Ag + and Cu 2+ ) have also been extensively studied due to their antimicrobial properties [ 57 ]. Ag + was found to have a high cytotoxic effect compared to Cu 2+ , while Cu 2+ ’s antibacterial effect remained only for a short time frame [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning antimicrobial activity, ions such as fluoride, 72 silver, 92,101,102 zinc, 91,103 magnesium and copper (F − , Ag + , Zn 2+ , Mg 2+ , Cu 2+ , respectively) were revealed to be a valid alternative when combined with HAp.…”
Section: Advanced Hap and Hap-hybrid Systemsmentioning
confidence: 99%
“…Their antibacterial effect is related to its electrostatic interaction with cell membranes resulting in its rupture. 92 Ag + is also highly referred to in the literature of doped HAp. 92,101,102 Sinulingga et al , 106 made two variations of 2.5% Ag + -doped HAp, one with Zn 2+ (2.5%) and another with Mg 2+ (2.5%), 92 in order to try to mitigate the cytotoxic effect found with previously reported 5% Ag + -doped HAp.…”
Section: Advanced Hap and Hap-hybrid Systemsmentioning
confidence: 99%
See 1 more Smart Citation